Pneumatic tire and manufacturing method thereof

JP7630763B2Active Publication Date: 2025-02-18SUMITOMO RUBBER INDUSTRIES LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020086536
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-05-18
Publication Date
2025-02-18
Estimated Expiration
2040-05-18

AI Technical Summary

Benefits of technology

【0030】 本発明によれば、金型に微細な凹凸加工を施すことなく、装着初期から優れたグリップ性能、特に、氷上グリップ性能を発揮させることができる空気入りタイヤの製造技術を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007630763000006
    Figure 0007630763000006
  • Figure 0007630763000001
    Figure 0007630763000001
  • Figure 0007630763000002
    Figure 0007630763000002
Patent Text Reader

Abstract

To provide a manufacturing technique for a pneumatic tire, by which excellent grip performance, particularly, grip performance on ice, from the beginning of mounting the tire can be exhibited without performing a fine recess and projection formation process on a mold.SOLUTION: In a pneumatic tire, a tread portion is formed of: a tread body portion composed of a tread rubber composition; and a surface layer portion composed of a rubber composition higher in polymer concentration than the tread rubber composition of the tread body portion, the surface layer portion containing a water-soluble inorganic filler. The pneumatic tire is a studless tire for a passenger car, in which is the tread portion is formed of a rubber composition containing a water-soluble inorganic filler. A manufacturing method for a pneumatic attire includes an inorganic filler spraying step of, between a molding step of molding a green tire and a vulcanizing step of vulcanizing the molded green tire, spraying a water-soluble inorganic filler to a surface of a tread portion of the molded green tire.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pneumatic tire that exhibits sufficient road grip performance immediately after being mounted on a vehicle, and a method for manufacturing the same. [Background technology]

[0002] 2. Description of the Related Art Pneumatic tires (hereinafter, simply referred to as "tires") are required to have sufficient road grip performance from the viewpoint of driving stability.

[0003] In recent years, studless tires have come into widespread use as tires for driving on snowy and icy roads. Because studless tires are used on snowy and icy roads, which have greater surface irregularities than general road surfaces, they are required to have even stricter grip performance (grip performance on ice) than regular tires.

[0004] As a result, a technique for improving grip performance on ice has been proposed in which a tread is formed using a rubber composition that has a water-soluble inorganic filler mixed in (Patent Documents 1 and 2). The water-soluble inorganic filler mixed in the tread dissolves when it comes into contact with moisture on the icy road surface, creating unevenness on the tire surface, thereby improving grip performance on ice.

[0005] It has also been proposed to modify the mold to form fine irregularities on the tread surface during tire vulcanization (Patent Document 3). These fine irregularities on the tire surface come into contact with the icy road surface, improving grip performance on ice. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 5592885 [Patent Document 2] Patent No. 5834086 [Patent Document 3] Patent No. 5456363 Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the case of the technologies shown in Patent Documents 1 and 2, even though water-soluble inorganic filler is mixed into the tread to give it sufficient grip performance on ice, sufficient grip performance on ice is not exhibited initially after installation, and sufficient grip performance on ice is not exhibited until after driving about 100 km on asphalt roads.

[0008] This problem of the tread's inherent grip performance not being realized unless the vehicle is fitted with the tread and driven a certain distance is not limited to the studless tires described above, but is the same for general tires.

[0009] On the other hand, while the technology shown in Patent Document 3 can provide excellent grip performance on ice from the initial stage of installation, it is not easy to apply fine uneven processing to a mold, and precise cleaning technology is required to maintain the uneven shape after processing, resulting in problems in terms of productivity and cost.

[0010] As described above, the conventional technologies are still not sufficient, and further improvements are required. In particular, in the case of studless tires, which are used on snowy and icy roads, the lack of grip performance on ice at the initial stage of installation is a major problem.

[0011] Therefore, an object of the present invention is to provide a manufacturing technology for pneumatic tires that can exhibit excellent grip performance, particularly grip performance on ice, from the initial stage of installation without the need for fine uneven processing on a mold. [Means for solving the problem]

[0012] The present inventors have conducted extensive research into solving the above problems, and have found that the above problems can be solved by the invention described below, thereby completing the present invention.

[0013] The invention described in claim 1 is The tread portion is formed by a tread main body portion made of a tread rubber composition and a surface layer portion made of a rubber composition having a higher polymer concentration than the tread rubber composition of the tread main body portion, The thickness of the surface layer is several tens to 100 μm, The pneumatic tire is characterized in that the surface layer portion contains 10 to 80 mass % of a water-soluble inorganic filler.

[0015] Claim 2 The invention described in The water-soluble inorganic filler in the surface layer of the tread portion is one of metal sulfates, metal chlorides, metal hydroxides, carbonates, and phosphates, or a mixture of two or more of them. 1 to The pneumatic tire is as described above.

[0016] Claim 3 The invention described in The water-soluble inorganic filler in the surface layer of the tread portion is a metal sulfate. 2 The pneumatic tire is as described above.

[0017] Claim 4 The invention described in The metal sulfate in the surface layer of the tread portion is magnesium sulfate. 3 The pneumatic tire is as described above.

[0018] Claim 5 The invention described in The magnesium sulfate is any one of anhydrous magnesium sulfate, magnesium sulfate dihydrate, and magnesium sulfate trihydrate, or a mixture of two or more of them. 4 The pneumatic tire is as described above.

[0019] Claim 6 The invention described in 2. The tire according to claim 1, wherein a water-insoluble inorganic filler is added to the surface layer of the tread portion in addition to the water-soluble inorganic filler. 5 13. The pneumatic tire according to claim 12,

[0020] Claim 7 The invention described in 2. The composition according to claim 1, wherein the content of the water-insoluble inorganic filler relative to the water-soluble inorganic filler is 3 to 30% by mass. 6 The pneumatic tire is as described above.

[0021] Claim 8 The invention described in The water-insoluble inorganic filler is one of egg shells, zinc oxide needle crystals, rice husks, talc, magnesium oxide, and iron powder, or a mixture of two or more of them. 6 or claims 7 The pneumatic tire is as described above.

[0022] Claim 9 The invention described in 10. A studless tire, wherein the tread portion is made of a rubber composition containing a water-soluble inorganic filler. 8 13. The pneumatic tire according to claim 12,

[0023] Claim 10 The invention described in The studless tire is a studless tire for a passenger car. 9 The pneumatic tire is as described above.

[0024] Claim 11 The invention described in The method for manufacturing a pneumatic tire is characterized in that, between a molding process for molding a raw tire and a vulcanization process for vulcanizing the molded raw tire, an inorganic filler spraying process is provided in which a water-soluble inorganic filler is sprayed onto the surface of a tread portion of the molded raw tire.

[0025] Claim 12 The invention described in 2. The tire according to claim 1, wherein the inorganic filler spraying step is a step of spraying the water-soluble inorganic filler on a surface of the tread portion by applying an aqueous solution of the water-soluble inorganic filler. 11 The present invention relates to a method for producing a pneumatic tire.

[0026] Claim 13 The invention described in 2. The tire according to claim 1, wherein the inorganic filler spraying step is a step of spraying the water-soluble inorganic filler by applying an organic solvent dispersion of the water-soluble inorganic filler to a surface of the tread portion. 11 The present invention relates to a method for producing a pneumatic tire.

[0027] Claim 14 The invention described in The organic solvent in the organic solvent dispersion is selected from the group consisting of a hydrocarbon organic solvent, anhydrous ethanol, and hexane, or a mixture of two or more of them. 13 The present invention relates to a method for producing a pneumatic tire.

[0028] Claim 15 The invention described in The inorganic filler scattering step is carried out so that the amount of the water-soluble filler scattered on the surface of the tread portion after drying is 0.005 to 0.04 g / cm 2 and applying and spraying the aqueous solution of the water-soluble inorganic filler or the organic solvent dispersion of the water-soluble inorganic filler. 12 or claims 14 1 is a method for producing a pneumatic tire according to any one of claims 1 to 9.

[0029] Claim 16 The invention described in 2. The method according to claim 1, wherein a water-insoluble inorganic filler is added to the aqueous solution of the water-soluble inorganic filler or the organic solvent dispersion of the water-soluble inorganic filler.12 or claims 15 1 is a method for producing a pneumatic tire according to any one of claims 1 to 9. Effect of the Invention

[0030] According to the present invention, it is possible to provide a manufacturing technique for pneumatic tires that can exhibit excellent grip performance, particularly grip performance on ice, from the initial stage of installation without the need for fine uneven processing on a mold. [Brief description of the drawings]

[0031] [Figure 1] 2 is an optical microscope photograph showing the observation result of the tread surface of a tire in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The present invention will be specifically described below based on the embodiment. Note that the following description will be based on a studless tire that is particularly effective when used on snowy and icy roads, but the same can be applied to general tires.

[0033] 1. Pneumatic tire according to the present embodiment The pneumatic tire according to this embodiment has a tread portion (hereinafter also referred to as "tread") formed of a tread main body portion made of a tread rubber composition and a surface layer portion made of a rubber composition having a higher polymer concentration than the tread rubber composition of the tread main body portion, and is characterized in that the surface layer portion contains a water-soluble inorganic filler (hereinafter also referred to as "water-soluble filler").

[0034] The present inventors have investigated the reason why in conventional tires, the inherent grip performance of the tread is not exhibited unless the tire is driven a certain distance after being mounted.

[0035] As a result, it was found that the tread of a vulcanized tire is not formed uniformly throughout with the tread rubber composition, but rather that a polymer-rich layer (hereinafter also referred to as the "skin layer") having a higher polymer concentration than the inner layer of the tread rubber composition is formed on the outermost surface of the tread with a thickness of about several tens to 100 μm, and that the inherent grip performance of the tread is not exhibited until this skin layer is removed and the tread is exposed.

[0036] That is, for example, in the case of studless tires, when they are first fitted, the skin layer, which is rich in polymer and has few surface irregularities, comes into contact with icy road surfaces and so does not provide sufficient grip performance on ice as a studless tire; it was found that only after driving about 100 km on asphalt roads and removing the skin layer can the tires provide sufficient grip performance on ice.

[0037] This phenomenon also occurs in ordinary tires other than studless tires, and it has been found that the presence of this skin layer inhibits the tire's grip performance in the initial period after installation.

[0038] Therefore, the inventors came up with the idea of ​​mixing a water-soluble filler into the skin layer. Specifically, the water-soluble filler is sprayed onto the surface of the tread of a raw tire before vulcanization, and then the tire is vulcanized. This allows the water-soluble filler to be incorporated into the skin layer, and a skin layer containing the water-soluble filler is formed on the surface of the tread, allowing the tire to exhibit sufficient grip performance even in the early stages of installation.

[0039] That is, when a water-soluble filler-rich skin layer is formed, a tire is formed in which a part of the water-soluble filler is exposed on the tread surface. When the tread of this tire comes into contact with water, the exposed water-soluble filler dissolves in the water, and voids are formed in the skin layer on the surface of the tread after the water-soluble filler dissolves, forming fine irregularities. When these fine irregularities come into contact with the road surface, water on the road surface is removed via the fine irregularities, so that sufficient grip performance can be achieved even immediately after mounting.

[0040] The formation of voids and the removal of water are repeated until the skin layer is gradually worn away and the original tread layer is revealed, maintaining the grip performance, after which the grip performance of the tread layer itself is fully exhibited. The skin layer rich in water-soluble fillers has lower abrasion resistance than conventional skin layers, so the skin layer wears away quickly and the tread layer appears in a short time. As a result, it is possible to achieve stable and sufficient grip performance from the initial installation. This decrease in abrasion resistance does not have much effect on the overall wear performance of the tire, since the skin layer is only 100 μm thick.

[0041] This effect is particularly evident in studless tires that run on snowy and icy roads where it is difficult to grip. As water on the snowy and icy road surface is removed via the fine irregularities, the tires are able to immediately provide sufficient grip performance on ice, even immediately after being fitted.

[0042] 2. Water-soluble inorganic filler Next, the water-soluble inorganic filler that is characteristically used in this embodiment will be described.

[0043] In the present embodiment, the water-soluble filler is not particularly limited, and any inorganic filler (preferably porous) that is soluble in water can be used. For example, a material having a solubility in water at room temperature (20°C) of 1 g / 100 g water or more can be used.

[0044] In general, the smaller the apparent density of a filler, the finer or more porous it is. Here, the nitrogen adsorption specific surface area (N2SA) of a filler indicates the pore surface area of ​​the filler. In general, when a particle has a smooth surface that is not porous, the median particle size (median diameter, D50) is 0.7 μm and the N2SA is 7 m. 2 / g, D50 is 0.5μm and N2SA is 15m 2 / g, D50 is 0.3μm and N2SA is 34m 2 / g. The magnesium sulfate used as a water-soluble filler in the examples described below has a D50 of 7.3 μm and an N2SA of 9.0 μm. 2 / g, it can be seen that the N2SA is large compared to the particle size and the sample is porous.

[0045] In this embodiment, the median particle size of the water-soluble filler is 100 μm or less, preferably 90 μm or less. It is more preferably 80 μm or less, and even more preferably 70 μm or less. It is particularly preferably 20 μm or less, and most preferably 10 μm or less. On the other hand, it is preferably 0.4 μm or more, more preferably 0.6 μm or more, and even more preferably 1.0 μm or more. Here, the median particle size (D50) can be measured by a laser diffraction method, and means the particle size at 50% of the integrated value in the mass-based particle size distribution curve obtained by a laser diffraction scattering method.

[0046] Specifically, the median particle size (D50) is measured by dispersing a water-soluble filler in a mixed solution of a dispersion solvent (toluene) and a dispersant (a 10% by mass solution of di-2-ethylhexyl sodium sulfosuccinate / toluene) at room temperature using a SALD-2000J model manufactured by Shimadzu Corporation. The dispersion is stirred for 5 minutes while being irradiated with ultrasonic waves to obtain a test liquid, which is then transferred to a batch cell and measured after 1 minute (refractive index: 1.70-0.20i).

[0047] From the viewpoint of the balance between grip performance and abrasion resistance, the apparent specific gravity of the water-soluble filler is 0.70 g / ml or less, preferably 0.65 g / ml or less. It is more preferably 0.62 g / ml or less. On the other hand, it is preferably 0.20 g / ml or more, more preferably 0.30 g / ml or more. It is even more preferably 0.40 g / ml or more, and particularly preferably 0.55 g / ml or more. Here, the apparent specific gravity is a value calculated from the mass when 30 ml of apparent volume is measured out in a 50 ml measuring cylinder.

[0048] In addition, from the viewpoints of particle stability, deliquescence resistance, and balance between grip performance and abrasion resistance, the water-soluble filler preferably has a low moisture content. Specifically, it is preferably 1.0% by mass or less, more preferably 0.8% by mass or less, even more preferably 0.3% by mass or less, and particularly preferably 0.1% by mass or less. Here, the moisture content is a value determined from the weight loss rate when left to stand in a thermostatic chamber at 250°C for 1 hour.

[0049] In addition, from the viewpoint of the balance between grip performance and abrasion resistance, the nitrogen adsorption specific surface area (N2SA) of the water-soluble filler is 1.3 m 2 / g or more, and 3.0m 2 / g or more is more preferable, and 4.0m 2 It is more preferable that the molecular weight is 5.0m / g or more. 2 It is particularly preferable that the amount is 8.0m / g or more. 2 / g or more is most preferable. 2 / g or less, and 2 / g or less is more preferable, 2 / g or less is more preferable. Here, N2SA is a value measured by the BET method in accordance with ASTM D3037-81, and the larger the N2SA, the more porous the material is, and the more effectively it can absorb moisture.

[0050] In the present embodiment, in consideration of not causing corrosion or damage to the vulcanization mold and of the impact on the environment including the human body, examples of the water-soluble filler include metal sulfates such as magnesium sulfate, sodium sulfate, potassium sulfate, etc.; metal chlorides such as potassium chloride, sodium chloride, calcium chloride, magnesium chloride, etc.; metal hydroxides such as potassium hydroxide, sodium hydroxide, etc.; carbonates such as potassium carbonate, sodium carbonate, calcium hydrogen carbonate, etc.; phosphates such as sodium hydrogen phosphate, sodium dihydrogen phosphate, etc. These may be used alone or in combination of two or more kinds.

[0051] Among the above-mentioned water-soluble fillers, metal sulfates are more preferred, and magnesium sulfate is even more preferred. Among magnesium sulfates, anhydrous magnesium sulfate, magnesium sulfate dihydrate, and magnesium sulfate trihydrate are preferred, and anhydrous magnesium sulfate is more preferred. Sodium sulfate is also preferred, and anhydrous sodium sulfate is more preferred. These may be used alone or in combination of two or more.

[0052] In this embodiment, the amount of the water-soluble filler scattered on the tread surface of the molded raw tire is 0.005 to 0.04 g / cm. 2 and preferably 0.01 to 0.03 g / cm 2 More preferably, it is 0.012 to 0.017 g / cm 2 By applying in such an amount, the content of the water-soluble filler in the skin layer can be set to 10 to 80% by mass, and appropriate surface grip performance can be exhibited from the initial stage of wearing the tire.

[0053] In this embodiment, a water-insoluble inorganic filler (hereinafter, also referred to as "water-insoluble filler") may be further added. Unlike water-soluble fillers, this water-insoluble filler does not dissolve when it comes into contact with water, but remains in the skin layer and scratches the road surface, so that the frictional resistance between the formed fine irregularities and the road surface (such as a snowy or icy road surface) becomes larger, and further, grip performance (especially grip performance on ice) is improved.

[0054] Specific examples of the water-insoluble filler include egg shells, tetrapod-type zinc oxide crystals, rice husks, talc, magnesium oxide, iron powder, etc., and the addition rate relative to the water-soluble filler is preferably 3 to 30 mass%, more preferably 5 to 20 mass%, and even more preferably 10 to 15 mass%. These may be used alone or in combination of two or more kinds.

[0055] The water-soluble filler described above can also be used in the tread rubber composition of a studless tire, and in this case, the content of the water-soluble filler is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, based on 100 parts by mass of the rubber component. On the other hand, it is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less. It is particularly preferably 20 parts by mass or less.

[0056] 3. Tread rubber composition As described above, during vulcanization, it is inevitable that a polymer-rich skin layer is formed on the tread surface of the tire, and the inherent grip performance of the tread cannot be exhibited immediately after installation. However, after a certain amount of running and the skin layer is removed, the inherent grip performance of the tread needs to be exhibited. Therefore, in the following, each material other than the water-soluble filler used in the tread rubber composition to exhibit the inherent grip performance of the tread will be described.

[0057] In this embodiment, the tread rubber composition includes a rubber component containing an isoprene-based rubber, a butadiene rubber, and a styrene-butadiene rubber, water-soluble fine particles, and a liquid plasticizer, and has a predetermined amount of styrene-butadiene rubber and liquid plasticizer.

[0058] (1) Rubber component In the present embodiment, examples of the rubber component of the tread rubber composition include diene rubbers such as isoprene rubber, butadiene rubber (BR), styrene butadiene rubber (SBR), styrene isoprene butadiene rubber (SIBR), acrylonitrile butadiene rubber (NBR), chloroprene rubber (CR), and butyl rubber (IIR). The rubber components may be used alone or in combination of two or more. Among them, SBR, BR, and isoprene rubber are preferred, and SBR and BR are more preferred.

[0059] The SBR is not particularly limited, and for example, those commonly used in the tire industry such as emulsion polymerization SBR (E-SBR), solution polymerization SBR (S-SBR), etc. These may be used alone or in combination of two or more.

[0060] Here, the rubber component preferably has a weight average molecular weight (Mw) of 150,000 or more, more preferably 350,000 or more, and preferably 4 million or less, more preferably 3 million or less. Here, the weight average molecular weight (Mw) is a value calculated in terms of standard polystyrene based on a measurement value obtained by gel permeation chromatography (GPC) (GPC-8000 series manufactured by Tosoh Corporation, detector: differential refractometer, column: TSKGEL SUPERMALTPORE HZ-M manufactured by Tosoh Corporation).

[0061] The styrene content of SBR is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more. On the other hand, it is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less. Here, the styrene content of SBR is 1 This value is calculated by H-NMR measurement.

[0062] The vinyl content of SBR (amount of 1,2-bonded butadiene units) is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 15% by mass or more. On the other hand, it is preferably 50% by mass or less, and more preferably 40% by mass or less. Here, the vinyl content of SBR refers to the vinyl content of the butadiene part (the number of vinyl group units in the butadiene structure), 1 This value is calculated by H-NMR measurement.

[0063] The SBR may be unmodified or modified. The modified SBR may be any SBR having a functional group that interacts with a filler such as silica, and examples of such modified SBR include terminal-modified SBR (terminal-modified SBR having the above-mentioned functional group at the terminal) in which at least one terminal of the SBR is modified with a compound (modifier) ​​having the above-mentioned functional group, main-chain-modified SBR having the above-mentioned functional group in the main chain, main-chain-terminal-modified SBR having the above-mentioned functional group in the main chain and at least one terminal (for example, main-chain-terminal-modified SBR having the above-mentioned functional group in the main chain and modified with the above-mentioned modifier at least one terminal), and terminal-modified SBR modified (coupled) with a polyfunctional compound having two or more epoxy groups in the molecule and having a hydroxyl group or an epoxy group introduced therein. These may be used alone or in combination of two or more.

[0064] Examples of the functional group include an amino group, an amide group, a silyl group, an alkoxysilyl group, an isocyanate group, an imino group, an imidazole group, a urea group, an ether group, a carbonyl group, an oxycarbonyl group, a mercapto group, a sulfide group, a disulfide group, a sulfonyl group, a sulfinyl group, a thiocarbonyl group, an ammonium group, an imide group, a hydrazo group, an azo group, a diazo group, a carboxyl group, a nitrile group, a pyridyl group, an alkoxy group, a hydroxyl group, an oxy group, and an epoxy group. These functional groups may have a substituent. Among them, an amino group (preferably an amino group in which a hydrogen atom of an amino group is substituted with an alkyl group having 1 to 6 carbon atoms), an alkoxy group (preferably an alkoxy group having 1 to 6 carbon atoms), an alkoxysilyl group (preferably an alkoxysilyl group having 1 to 6 carbon atoms), and an amide group are preferred.

[0065] As the SBR, oil-extended SBR or non-oil-extended SBR can be used. When oil-extended SBR is used, the amount of oil extension of SBR, i.e., the content of oil extension oil contained in SBR, is preferably 10 to 50 parts by mass per 100 parts by mass of rubber solid content of SBR.

[0066] The glass transition temperature (Tg) of SBR is preferably -90°C or higher, and more preferably -50°C or higher. On the other hand, it is preferably 0°C or lower, and more preferably 10°C or lower. The glass transition temperature is a value obtained by measuring at a heating rate of 10°C / min using a differential scanning calorimeter (Q200) manufactured by TA Instruments Japan, in accordance with JIS-K7121.

[0067] As the SBR, for example, SBR manufactured and sold by Sumitomo Chemical Co., Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, and the like can be used.

[0068] The content of SBR in 100% by mass of the rubber component is preferably 40% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, while it is preferably 95% by mass or less, and more preferably 90% by mass or less.

[0069] The BR is not particularly limited, and may be, for example, a BR having a high cis content, a BR containing 1,2-syndiotactic polybutadiene crystals (SPB-containing BR), butadiene rubber synthesized using a rare earth catalyst (rare earth-based BR), or a tin-modified butadiene rubber modified with a tin compound (tin-modified BR), which are commonly used in the tire industry. These may be used alone or in combination of two or more. Among these, rare earth-based BR is preferred.

[0070] Rare earth BR is a butadiene rubber synthesized using a rare earth catalyst, and is characterized by a high cis content and a low vinyl content. General-purpose products used in tire manufacturing can be used as rare earth BR.

[0071] The rare earth element catalyst may be a known one, for example, a catalyst containing a lanthanum series rare earth element compound, an organoaluminum compound, an aluminoxane, a halogen-containing compound, or a Lewis base as required. Among them, a neodymium (Nd)-containing compound is particularly preferred as the lanthanum series rare earth element compound.

[0072] The cis content (amount of cis-1,4-bonded butadiene units) of BR is preferably 90% by mass or more, more preferably 93% by mass or more, and even more preferably 95% by mass or more. Here, the cis content is a value calculated by infrared absorption spectrum analysis.

[0073] The vinyl content (amount of 1,2-bonded butadiene units) of the BR is preferably 1.8% by mass or less, more preferably 1.0% by mass or less, further preferably 0.5% by mass or less, and particularly preferably 0.3% by mass or less.

[0074] The BR may be either unmodified or modified. The modified BR may be a modified BR having a functional group introduced therein similar to the modified SBR described above.

[0075] As the BR, for example, products from Ube Industries, Ltd., JSR Corporation, Asahi Kasei Corporation, Zeon Corporation, etc. can be used.

[0076] The BR content in 100% by mass of the rubber component is preferably 5% by mass or more, and more preferably 10% by mass or more, while it is preferably 60% by mass or less, more preferably 50% by mass or less, and further preferably 30% by mass or less.

[0077] Examples of isoprene-based rubber include natural rubber (NR), isoprene rubber (IR), modified NR, modified NR, and modified IR. Examples of NR include SIR20, RSS#3, and TSR20, which are common in the tire industry. Examples of IR include IR2200, which are common in the tire industry, and are not particularly limited. Examples of modified NR include deproteinized natural rubber (DPNR), high-purity natural rubber (UPNR), and the like. Examples of modified NR include epoxidized natural rubber (ENR), hydrogenated natural rubber (HNR), and grafted natural rubber. Examples of modified IR include epoxidized isoprene rubber, hydrogenated isoprene rubber, and grafted isoprene rubber. These may be used alone or in combination of two or more. Of these, natural rubber is preferred.

[0078] The total content of SBR and BR in 100% by mass of the rubber component is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, particularly preferably 90% by mass or more, and most preferably 100% by mass.

[0079] (2) Wax In the present embodiment, the tread rubber composition preferably contains a wax. The wax is not particularly limited, and examples thereof include petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable waxes such as candelilla wax, carnauba wax, Japan wax, rice wax, and jojoba wax; and animal waxes such as beeswax, lanolin, and spermaceti; mineral waxes such as ozokerite, ceresin, and petrolactam; and synthetic waxes such as polymers of ethylene and propylene. These may be used alone or in combination of two or more. Among them, petroleum waxes are preferred, and paraffin wax and microcrystalline wax are more preferred. In addition, it is preferred that the content of branched alkanes in 100% by mass of microcrystalline wax is 50% by mass or more.

[0080] As the wax, for example, products available from Ouchi Shinko Chemical Industry Co., Ltd., Nippon Seiro Co., Ltd., Seiko Chemical Co., Ltd., etc. can be used.

[0081] The content of the paraffin wax per 100 parts by mass of the rubber component is preferably 2.3 parts by mass or less, more preferably 2.0 parts by mass or less, even more preferably 1.5 parts by mass or less, and particularly preferably 1.3 parts by mass or less. On the other hand, it is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 0.8 parts by mass or more, and particularly preferably 1.0 part by mass or more.

[0082] The content of the microcrystalline wax per 100 parts by mass of the rubber component is preferably 0.3 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 0.8 parts by mass or more, and particularly preferably 1.0 parts by mass or more. On the other hand, the content is preferably 3 parts by mass or less, more preferably 2 parts by mass or less, and even more preferably 1.5 parts by mass or less.

[0083] (3) Antiaging Agents In the present embodiment, the tread rubber composition preferably contains an antioxidant. The antioxidant is not particularly limited, but examples thereof include naphthylamine-based antioxidants such as phenyl-α-naphthylamine, diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine, N-isopropyl-N'-phenyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p-phenylenediamine, and the like. Examples of the antioxidants include p-phenylenediamine antioxidants such as p-phenylenediamine; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. These may be used alone or in combination of two or more. Among them, phenylenediamine antioxidants are preferred because they have a high migration rate to the surface layer and are excellent in the spreading function, and N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine and N,N'-bis-(1,4-dimethylpentyl)-p-phenylenediamine are more preferred. A quinoline-based antioxidant may be used in combination with the phenylenediamine-based antioxidant; however, the quinoline-based antioxidant has a slower migration rate than the phenylenediamine-based antioxidant, and tends to have a lower softening effect on the surface layer.

[0084] As the antioxidant, for example, products available from Seiko Chemical Co., Ltd., Sumitomo Chemical Co., Ltd., Ouchi Shinko Chemical Industry Co., Ltd., Flexis, etc. can be used.

[0085] The amount of the phenylenediamine-based antioxidant per 100 parts by mass of the rubber component is preferably 2.1 parts by mass or more, and more preferably 2.4 parts by mass or more, while it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 7 parts by mass or less.

[0086] The total content of the antioxidants per 100 parts by mass of the rubber component is preferably 2 parts by mass or more, and more preferably 2.4 parts by mass or more, while it is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and further preferably 8 parts by mass or less.

[0087] (4) Liquid plasticizer In the present embodiment, the tread rubber composition preferably contains a liquid plasticizer. The liquid plasticizer is not particularly limited as long as it is a plasticizer that is in a liquid state at 20°C, and examples thereof include oil, liquid resin, and liquid polymer. These may be used alone or in combination of two or more kinds. Among them, oil and liquid resin are preferred.

[0088] The content of the liquid plasticizer per 100 parts by mass of the rubber component is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 25 parts by mass or more. It is particularly preferably 35 parts by mass or more. On the other hand, it is preferably 100 parts by mass or less, more preferably 80 parts by mass or less, and even more preferably 60 parts by mass or less. It is particularly preferably 50 parts by mass or less. In this specification, the content of the liquid plasticizer includes the amount of oil contained in the oil-extended rubber.

[0089] Examples of the oil include process oil, vegetable oil, and mixtures thereof. Examples of the process oil include paraffin-based process oil, aromatic process oil, naphthenic process oil, mild extraction solvates (MES), and treated distillate aromatic extracts (TDAE). Examples of the vegetable oil include castor oil, cottonseed oil, linseed oil, rapeseed oil, soybean oil, palm oil, coconut oil, peanut oil, rosin, pine oil, pine tar, tall oil, corn oil, rice oil, safflower oil, sesame oil, olive oil, sunflower oil, palm kernel oil, camellia oil, jojoba oil, macadamia nut oil, tung oil, and oleic acid-containing oil. These may be used alone or in combination of two or more. Among them, process oil is preferred, and aromatic process oil and oleic acid-containing oil are preferred.

[0090] As the oil, for example, products from Idemitsu Kosan Co., Ltd., Sankyo Yuka Kogyo Co., Ltd., Japan Energy Co., Ltd., Orisoi Co., Ltd., H&R Co., Ltd., Toyokuni Oil Mills Co., Ltd., Showa Shell Sekiyu K.K., Fuji Kosan Co., Ltd., etc. can be used.

[0091] Examples of liquid resins include terpene resins (including terpene phenol resins and aromatic modified terpene resins) that are liquid at 20°C, styrene resins, C5 resins, C9 resins, C5 / C9 resins, dicyclopentadiene (DCPD) resins, coumarone indene resins (including coumarone and indene simple resins), phenol resins, olefin resins, polyurethane resins, and acrylic resins. These may be used alone or in combination of two or more. Among these, coumarone indene resins are preferred.

[0092] Examples of liquid polymers (liquid diene-based polymers) include liquid styrene butadiene copolymers (liquid SBR), liquid butadiene polymers (liquid BR), liquid isoprene polymers (liquid IR), liquid styrene isoprene copolymers (liquid SIR), liquid styrene butadiene styrene block copolymers (liquid SBS block polymers), liquid styrene isoprene styrene block copolymers (liquid SIS block polymers), liquid farnesene polymers, and liquid farnesene butadiene copolymers that are in a liquid state at 20°C. The terminals or main chains of these may be modified with polar groups. These may be used alone or in combination of two or more.

[0093] (5) Resin In this embodiment, the tread rubber composition preferably contains a resin (solid resin: a resin that is in a solid state at room temperature (25° C.)).

[0094] The softening point of the resin is preferably 60° C. or higher, more preferably 65° C. or higher, and even more preferably 80° C. or higher. On the other hand, it is preferably 160° C. or lower, and more preferably 135° C. or lower. The softening point of the resin is the temperature at which the ball drops when the softening point specified in JIS K 6220-1:2001 is measured using a ring and ball softening point measuring device.

[0095] The resin (solid resin) is not particularly limited, but examples thereof include aromatic vinyl polymers, coumarone-indene resins, terpene resins, dicyclopentadiene resins (DCPD resins), C5 petroleum resins, C9 petroleum resins, C5 / C9 petroleum resins, pt-butylphenol acetylene resins, acrylic resins, and the like. These may be used alone or in combination of two or more. The resin may be hydrogenated. Among these, aromatic vinyl polymers and terpene resins are preferred.

[0096] An aromatic vinyl polymer is a resin obtained by polymerizing α-methylstyrene and / or styrene, and examples include a homopolymer of styrene (styrene resin), a homopolymer of α-methylstyrene (α-methylstyrene resin), a copolymer of α-methylstyrene and styrene, and a copolymer of styrene and other monomers.

[0097] Coumarone-indene resin is a resin that contains coumarone and indene as the main monomer components that make up the resin skeleton (main chain). Other monomer components contained in the skeleton besides coumarone and indene include styrene, α-methylstyrene, methylindene, vinyltoluene, etc.

[0098] The terpene resin is not particularly limited as long as it is a resin having a unit derived from a terpene compound, and examples thereof include polyterpene (a resin obtained by polymerizing a terpene compound), terpene aromatic resin (a resin obtained by copolymerizing a terpene compound and an aromatic compound), and aromatic modified terpene resin (a resin obtained by modifying a terpene resin with an aromatic compound). These may be used alone or in combination of two or more kinds. Among them, terpene aromatic resin and aromatic modified terpene resin are preferred, and aromatic modified terpene resin is more preferred.

[0099] The above terpene compound is (C5H8) n The hydrocarbons and their oxygen-containing derivatives are represented by the following composition: Monoterpenes (C 10 H 16 ), sesquiterpenes (C 15 H 24 ), diterpenes (C 20 H 32 ), and examples thereof include α-pinene, β-pinene, dipentene, limonene, myrcene, alloocimene, ocimene, α-phellandrene, α-terpinene, γ-terpinene, terpinolene, 1,8-cineole, 1,4-cineole, α-terpineol, β-terpineol, and γ-terpineol.

[0100] The above-mentioned terpene compounds also include resin acids (rosin acids) such as abietic acid, neoabietic acid, palustric acid, levopimaric acid, pimaric acid, and isopimaric acid. That is, the above-mentioned terpene resins also include rosin resins whose main component is rosin acid obtained by processing pine resin. Examples of rosin resins include naturally occurring rosin resins (polymerized rosins) such as gum rosin, wood rosin, and tall oil rosin, as well as modified rosin resins such as maleic acid-modified rosin resins and rosin-modified phenolic resins, rosin esters such as rosin glycerin esters, and disproportionated rosin resins obtained by disproportionating rosin resins.

[0101] The aromatic compound is not particularly limited as long as it is a compound having an aromatic ring, and examples thereof include phenolic compounds such as phenol, alkylphenol, alkoxyphenol, and unsaturated hydrocarbon group-containing phenol; naphthol compounds such as naphthol, alkylnaphthol, alkoxynaphthol, and unsaturated hydrocarbon group-containing naphthol; styrene derivatives such as styrene, alkylstyrene, alkoxystyrene, and unsaturated hydrocarbon group-containing styrene; etc. Among these, styrene is preferred.

[0102] Examples of the above resins and liquid resins that can be used include products from Maruzen Petrochemical Co., Ltd., Sumitomo Bakelite Co., Ltd., Yasuhara Chemical Co., Ltd., Tosoh Corporation, Rutgers Chemicals, BASF, Arizona Chemical Company, Nippon Paint Chemical Co., Ltd., Nippon Shokubai Co., Ltd., JX Energy Corporation, Arakawa Chemical Industries, Ltd., and Taoka Chemical Co., Ltd.

[0103] The resin content is preferably 3 parts by mass or more, more preferably 4 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. On the other hand, it is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less, and particularly preferably 30 parts by mass or less.

[0104] (6) Other materials In this embodiment, the tread rubber composition preferably contains an amide compound and / or a nonionic surfactant having an SP value of 9.0 or more.

[0105] The amide compound is not particularly limited, but may be fatty acid amide or fatty acid amide ester. These may be used alone or in combination of two or more. Among them, fatty acid amide is preferred, and a mixture of fatty acid amide and fatty acid amide ester is more preferred.

[0106] The amide compound may be a mixture with a fatty acid metal salt, and it is preferable that the amide compound is a mixture with a fatty acid metal salt, because the effect can be more suitably obtained.

[0107] Examples of metals constituting fatty acid metal salts include potassium, sodium, magnesium, calcium, barium, zinc, nickel, and molybdenum. These may be used alone or in combination of two or more. Among these, alkaline earth metals such as calcium and zinc are preferred, and calcium is more preferred.

[0108] The fatty acid constituting the fatty acid metal salt may be a saturated fatty acid or an unsaturated fatty acid. Examples of the saturated fatty acid include decanoic acid, dodecanoic acid, and stearic acid, and examples of the unsaturated fatty acid include oleic acid and elaidic acid. These may be used alone or in combination of two or more. Among them, saturated fatty acids are preferred, and stearic acid is more preferred. Also, the unsaturated fatty acid is preferred to be oleic acid.

[0109] The fatty acid amide may be a saturated fatty acid amide or an unsaturated fatty acid amide, and examples of the saturated fatty acid amide include stearic acid amide and behenic acid amide, and examples of the unsaturated fatty acid amide include oleic acid amide and erucic acid amide. These may be used alone or in combination of two or more. Among them, unsaturated fatty acid amide is preferred, and oleic acid amide is more preferred.

[0110] The fatty acid amide ester may be a saturated fatty acid amide ester or an unsaturated fatty acid amide ester, and examples of the saturated fatty acid amide ester include stearic acid amide ester and behenic acid amide ester, and examples of the unsaturated fatty acid amide ester include oleic acid amide ester and erucic acid amide ester. These may be used alone or in combination of two or more. Among them, unsaturated fatty acid amide ester is preferred, and oleic acid amide ester is more preferred.

[0111] As the amide compound, for example, products available from NOF Corp., Struktol, LANXESS, etc. can be used.

[0112] The content of the amide compound relative to 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 0.8 parts by mass or more. On the other hand, it is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, and even more preferably 3 parts by mass or less. It is particularly preferably 2 parts by mass or less. Note that, when the amide compound is a mixture with a fatty acid metal salt, the content of the amide compound includes the amount of the fatty acid metal salt contained in the amide compound.

[0113] The nonionic surfactant having an SP value of 9.0 or more is not particularly limited, and examples thereof include nonionic surfactants represented by the following formula (1) and / or the following formula (2); Pluronic nonionic surfactants; sorbitan fatty acid esters such as polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tristearate, and polyoxyethylene sorbitan tripalmitate; polyoxyethylene dodecyl ether, polyoxyethylene lauryl ether, polyoxyethylene 2-ethylhexyl ether, polyoxyethylene oleyl ether, ethylene glycol dibutyl ether, ethylene glycol dilauryl ether, ethylene glycol di-2-ethylhexyl ether, and ethylene glycol dioleyl ether. These nonionic surfactants may be used alone or in combination of two or more. Among them, Pluronic nonionic surfactants are more preferable.

[0114] [ka] (In formula (1), R l represents a hydrocarbon group having 6 to 26 carbon atoms. d represents an integer.

[0115] [ka] (In formula (2), R 2 and R 3 are the same or different and represent a hydrocarbon group having 6 to 26 carbon atoms. e represents an integer.

[0116] Examples of the nonionic surfactant represented by the above formula (1) include ethylene glycol monooleate, ethylene glycol monopalmiate, ethylene glycol monopalmitate, ethylene glycol monopaccenate, ethylene glycol monolinoleate, ethylene glycol monolinolenate, ethylene glycol monoarachidonate, ethylene glycol monostearate, ethylene glycol monocetylate, and ethylene glycol monolaurate.

[0117] Examples of the nonionic surfactant represented by the above formula (2) include ethylene glycol dioleate, ethylene glycol dipalmiate, ethylene glycol dipalmitate, ethylene glycol dipaccenate, ethylene glycol dilinoleate, ethylene glycol dilinolenate, ethylene glycol diarachidonate, ethylene glycol distearate, ethylene glycol dicetylate, and ethylene glycol dilaurate.

[0118] The above Pluronic type nonionic surfactants are also called polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxypropylene block polymers, and polypropylene glycol ethylene oxide adducts, and are generally nonionic surfactants represented by the following formula (I): As represented by the following formula (I), Pluronic type nonionic surfactants have hydrophilic groups composed of ethylene oxide structures on both sides, and have hydrophobic groups composed of propylene oxide structures sandwiched between the hydrophilic groups.

[0119] [ka] (In formula (I), a, b, and c represent integers.)

[0120] The degree of polymerization of the polypropylene oxide block of the Pluronic nonionic surfactant (b in the above formula (I)) and the amount of polyethylene oxide added (a+c in the above formula (I)) are not particularly limited and can be appropriately selected according to the use conditions, purpose, etc. The higher the proportion of the polypropylene oxide block, the higher the affinity with rubber and the slower the rate of migration to the rubber surface. The degree of polymerization of the polypropylene oxide block is preferably 100 or less, more preferably 10 to 70, and even more preferably 10 to 60. It is particularly preferably 20 to 60, and most preferably 20 to 45. Similarly, the amount of polyethylene oxide added is preferably 100 or less, more preferably 3 to 65, and even more preferably 5 to 55. It is particularly preferably 5 to 40, and most preferably 10 to 40.

[0121] Examples of pluronic-type nonionic surfactants include the Pluronic series manufactured by BASF Japan Ltd., the Newpol PE series manufactured by Sanyo Chemical Industries Ltd., the Adeka Pluronic L or F series manufactured by Asahi Denka Kogyo Co., Ltd., the Epan series manufactured by Daiichi Kogyo Seiyaku Co., Ltd., the Pronon series or Unilube manufactured by NOF Corp., etc. These may be used alone or in combination of two or more kinds.

[0122] The greater the difference between the SP value of the nonionic surfactant and the SP value of the rubber component, the more preferable. Specifically, the difference is preferably 9.0 to 12, more preferably 9.1 to 11, and even more preferably 9.2 to 10.5.

[0123] The SP value means a solubility parameter calculated by the Hoy method based on the structure of a compound. The Hoy method is a calculation method described in, for example, KL Hoy "Table of Solubility Parameters", Solvent and Coatings Materials Research and Development Department, Union Carbites Corp. (1985).

[0124] The content of the nonionic surfactant having an SP value of 9.0 or more per 100 parts by mass of the rubber component is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, and further preferably 0.8 to 2 parts by mass.

[0125] The rubber composition may contain a reinforcing filler such as silica, carbon black, etc. By containing these fillers, an appropriate hardness is imparted to the tread rubber composition.

[0126] Examples of silica include dry silica (anhydrous silicic acid) and wet silica (hydrated silicic acid), among which wet silica is preferred because it has a large number of silanol groups. These may be used alone or in combination of two or more.

[0127] The nitrogen adsorption specific surface area (N2SA) of silica is 80m 2 / g or more, and 2 / g or more is more preferable, and 150m 2 / g or more is more preferable. 2 / g or more, 200m 2 / g or more, 220m 2 / g or more, it becomes more preferable, and 230m 2 / g or more is most preferable. 2 / g or less, and 2 / g or less is more preferable, and 2 It is more preferable that the N2SA of silica is not more than 1 / g. The N2SA of silica is a value measured by the BET method in accordance with ASTM D3037-81.

[0128] As the silica, for example, products manufactured by Degussa, Rhodia, Tosoh Silica Co., Ltd., Solvay Japan Co., Ltd., Tokuyama Corporation, etc. can be used.

[0129] 220m 2The content of silica of 100 parts by mass of the rubber component is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less, based on 100 parts by mass of the rubber component.

[0130] The total content of silica is preferably 30 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 60 parts by mass or more, and particularly preferably 80 parts by mass or more, based on 100 parts by mass of the rubber component. On the other hand, it is preferably 200 parts by mass or less, more preferably 160 parts by mass or less, and even more preferably 150 parts by mass or less, and particularly preferably 130 parts by mass or less.

[0131] In the tread rubber composition of the present embodiment, the content of silica in 100% by mass of the filler (reinforcing filler) is preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more. It is particularly preferably 90% by mass or more. The upper limit is not particularly limited, and may be 100% by mass.

[0132] When the tread rubber composition of the present embodiment contains silica, it is preferable that it further contains a silane coupling agent. The silane coupling agent is not particularly limited, and examples thereof include bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(4-triethoxysilylbutyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(2-triethoxysilylethyl)trisulfide, bis(4-trimethoxysilylbutyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(2-triethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, bis(2-trimethoxysilylethyl)disulfide, bis(4-trimethoxysilylbutyl)disulfide, 3-trimethoxysilylpropyl-N Examples of such silanes include sulfide-based silanes such as 3-mercaptopropyltrimethoxysilane, 2-mercaptoethyltriethoxysilane, vinyl-based silanes such as vinyltriethoxysilane, vinyltrimethoxysilane, amino-based silanes such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, glycidoxy-based silanes such as γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, nitro-based silanes such as 3-nitropropyltrimethoxysilane, 3-nitropropyltriethoxysilane, and chloro-based silanes such as 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane. Commercially available products include those manufactured by Degussa, Momentive, Shin-Etsu Silicones, Tokyo Chemical Industry, Azumax, and Dow Corning Toray Co., Ltd. These may be used alone or in combination of two or more.

[0133] The content of the silane coupling agent is preferably 3 parts by mass or more, more preferably 5 parts by mass or more, relative to 100 parts by mass of silica, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less.

[0134] The carbon black is not particularly limited, and examples thereof include N134, N110, N220, N234, N219, N339, N330, N326, N351, N550, and N762. These may be used alone or in combination of two or more kinds.

[0135] The nitrogen adsorption specific surface area (N2SA) of carbon black is 80m 2 / g or more, and 2 / g or more is more preferable. 2 / g or less, and 2 / g or less is more preferable, and 150m 2 / g or less is more preferable. 2 It is particularly preferable that the N2SA of carbon black is equal to or less than 1 / g. The N2SA of carbon black is a value determined according to JIS K6217-2:2001.

[0136] As carbon black, for example, products manufactured by Asahi Carbon Co., Ltd., Cabot Japan Co., Ltd., Tokai Carbon Co., Ltd., Mitsubishi Chemical Corporation, Lion Corporation, Shinnikka Carbon Co., Ltd., Columbia Carbon Company, etc. can be used.

[0137] The amount of carbon black is preferably 3 parts by mass or more, and more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. On the other hand, the amount is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less, particularly preferably 20 parts by mass or less, and most preferably 10 parts by mass or less.

[0138] The tread rubber composition of the present embodiment may contain aluminum hydroxide, alumina, magnesium oxide, talc, and diatomaceous earth as a reinforcing filler.

[0139] The nitrogen adsorption specific surface area (N2SA) of aluminum hydroxide is 3 to 60 m 2 / g, and 6 to 50m 2 / g is more preferable, and 10 to 40m 2 It is more preferable that the molecular weight is / g.

[0140] Aluminum hydroxide is poorly water-soluble, has little coagulation in a rubber composition, and usually exists as a single particle in the rubber composition. Therefore, it does not impair the reinforcing properties of the rubber. The N2SA of aluminum hydroxide is a value measured by the BET method according to ASTM D3037-81.

[0141] The content of aluminum hydroxide is preferably 3 parts by mass or more, and more preferably 4 parts by mass or more, based on 100 parts by mass of the rubber component. On the other hand, it is preferably 60 parts by mass or less, more preferably 50 parts by mass or less, and even more preferably 40 parts by mass or less, particularly preferably 20 parts by mass or less, and most preferably 15 parts by mass or less.

[0142] The tread rubber composition of the present embodiment may contain a fatty acid, preferably stearic acid. As the stearic acid, a conventionally known product can be used, for example, a product of NOF Corporation, NOF Corporation, Kao Corporation, FUJIFILM Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., etc. can be used.

[0143] The content of the fatty acid (preferably stearic acid) per 100 parts by mass of the rubber component is preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more, and is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0144] The tread rubber composition of the present embodiment may contain zinc oxide. As the zinc oxide, a conventionally known product can be used, for example, a product of Mitsui Mining & Smelting Co., Ltd., Toho Zinc Co., Ltd., Hakusui Tech Co., Ltd., Seido Chemical Industry Co., Ltd., Sakai Chemical Industry Co., Ltd., etc. can be used.

[0145] The amount of zinc oxide is preferably 0.5 parts by mass or more, and more preferably 1 part by mass or more, based on 100 parts by mass of the rubber component, and is preferably 10 parts by mass or less, and more preferably 5 parts by mass or less.

[0146] The tread rubber composition of the present embodiment may contain sulfur. Examples of sulfur include powdered sulfur, precipitated sulfur, colloidal sulfur, insoluble sulfur, highly dispersible sulfur, and soluble sulfur, which are generally used in the rubber industry. These may be used alone or in combination of two or more kinds.

[0147] As sulfur, for example, products from Tsurumi Chemical Industry Co., Ltd., Karuizawa Sulfur Co., Ltd., Shikoku Chemical Industry Co., Ltd., Flexis Corporation, Nippon Kanritsu Kogyo Co., Ltd., Hosoi Chemical Industry Co., Ltd., etc. can be used.

[0148] The amount of sulfur per 100 parts by mass of the rubber component is preferably 0.1 parts by mass or more, and more preferably 0.5 parts by mass or more, and is preferably 5 parts by mass or less, and more preferably 3 parts by mass or less.

[0149] The tread rubber composition of the present embodiment may contain a vulcanization accelerator. Examples of the vulcanization accelerator include thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, di-2-benzothiazolyl disulfide, and N-cyclohexyl-2-benzothiaryl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram disulfide (TMTD), tetrabenzylthiuram disulfide (TBzTD), and tetrakis(2-ethylhexyl)thiuram disulfide (TOT-N); sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazolyl sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N-oxyethylene-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenyl guanidine, di-orthotolyl guanidine, and orthotolyl biguanidine. These may be used alone or in combination of two or more. Among them, sulfenamide vulcanization accelerators and guanidine vulcanization accelerators are preferred, and it is preferred to use a sulfenamide vulcanization accelerator and a guanidine vulcanization accelerator in combination.

[0150] As the vulcanization accelerator, for example, products manufactured by Kawaguchi Chemical Co., Ltd., Ouchi Shinko Chemical Co., Ltd., etc. can be used.

[0151] The content of the vulcanization accelerator is preferably 1 part by mass or more, and more preferably 2 parts by mass or more, based on 100 parts by mass of the rubber component, while it is preferably 10 parts by mass or less, and more preferably 7 parts by mass or less.

[0152] The tread rubber composition of the present embodiment may further contain additives generally used in the tire industry, such as organic peroxides, fillers such as calcium carbonate, clay, mica, etc. The content of these additives is preferably 0.1 to 200 parts by mass or more per 100 parts by mass of the rubber component.

[0153] In the present embodiment, the tread rubber composition can be produced by a known method, for example, by kneading the above-mentioned materials using a rubber kneading device such as an open roll or a Banbury mixer, and then extrusion processing is performed according to the shape of the tread to form the tread.

[0154] As for the kneading conditions, in the base kneading step in which additives other than the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 100 to 180°C, preferably 120 to 170°C, and the kneading time is usually 30 seconds to 30 minutes, preferably 1 minute to 30 minutes. In the finish kneading step in which the vulcanizing agent and the vulcanization accelerator are kneaded, the kneading temperature is usually 120°C or lower, preferably room temperature 80 to 110°C. Furthermore, the composition kneaded with the vulcanizing agent and the vulcanization accelerator is usually subjected to a vulcanization treatment such as press vulcanization. In the case of passenger car tires (PC tires), the vulcanization temperature is usually 140 to 190°C, and the vulcanization time is usually 5 to 15 minutes.

[0155] 4. Manufacturing of tires according to the present embodiment Next, the manufacture of the tire according to the present embodiment will be described.

[0156] (1) Raw tire molding process First, a green tire is formed by molding a tread formed from the above tread rubber composition and other tire components separately prepared in a tire building machine by a normal method.

[0157] (2) Water-soluble filler spraying process Next, a water-soluble filler solution or organic solvent dispersion (hereinafter collectively referred to as "water-soluble filler solution") is applied to the tread surface of the green tire. At this time, the amount of the water-soluble filler dispersed on the tread surface after drying is 0.005 to 0.04 g / cm. 2 The amount of application is adjusted so that the applied water-soluble filler liquid dries, causing the water-soluble filler particles to precipitate on the tread surface, thereby providing a raw tire in which the above-mentioned amount of water-soluble filler is dispersed on the tread surface.

[0158] In this case, the concentration of the water-soluble filler in the water-soluble filler liquid may be set in consideration of the ease of application to the tread surface, but it is usually preferable to adjust the concentration to 10 to 30 mass %.

[0159] When the water-soluble filler liquid is prepared as an organic solvent dispersion, it is preferable to use any one of a hydrocarbon organic solvent, anhydrous ethanol, hexane, etc. as the organic solvent, and these may also be used as a mixed solvent.

[0160] As described above, a water-insoluble filler may be added in an amount of 5 to 15% by mass relative to the water-soluble filler together with the water-soluble filler.

[0161] As a specific means for applying the composition to the tread surface, known means such as brush application or spray application can be used.

[0162] (3) Vulcanization process Next, the raw tire with the water-soluble filler scattered on the tread surface is set in a predetermined vulcanization mold and heated and pressurized using a vulcanization device.

[0163] At this time, as described above, a skin layer is formed on the surface of the tread. In this embodiment, however, since the water-soluble filler is dispersed on the tread surface, the water-soluble filler is mixed into the skin layer, resulting in a tire in which some of the water-soluble filler is exposed on the tread surface.

[0164] When the tread of such a tire comes into contact with water, the exposed water-soluble filler dissolves from the skin layer to form voids with an average diameter of 0.1 to 100 μm on the tread surface, forming fine irregularities, so that the tire can immediately exhibit sufficient grip performance on ice even immediately after mounting. The voids preferably have an average diameter of 0.1 to 100 μm, but from the viewpoints of steering stability and grip performance on ice, it is more preferable that the average diameter is 1 to 80 μm, and even more preferable that the average diameter is 10 to 70 μm.

[0165] The average void diameter can be measured by observation with a scanning electron microscope (SEM). Specifically, a photograph is taken with the scanning electron microscope, and the diameter is determined as the diameter of the sphere if the void shape is spherical, the minor axis if the void shape is needle-like or rod-like, and the average diameter from the center if the void shape is irregular, and the average value of the diameters of 100 voids is determined as the average diameter.

[0166] By manufacturing the tire according to the present embodiment based on each of the above steps, it is possible to provide a tire that exhibits sufficient grip performance (especially grip performance on ice) even in the initial period after mounting, and a tire that is particularly suitable as a passenger car tire (PC tire) or a studless tire (winter tire) can be provided. EXAMPLES

[0167] The present invention will now be described in more detail with reference to examples. In these examples, raw tires were made using tread rubber compositions of the same composition, and the difference in grip performance on ice depending on whether or not a water-soluble filler was dispersed on the tread surface was measured.

[0168] 1. Preparation of tires for evaluation (Examples and Comparative Examples) First, tires for evaluation (Example and Comparative Example) were produced.

[0169] The various chemicals used in the examples and comparative examples are described below. <sbr1>: N9548 manufactured by Zeon Co., Ltd. (styrene content: 35% by mass, vinyl content: 18% by mass, contains 37.5 parts by mass of oil per 100 parts by mass of rubber solids) <sbr2>NS612 manufactured by Zeon Corporation (styrene content: 15% by mass, vinyl content: 30% by mass) : BUNA-CB25 manufactured by LANXESS Co., Ltd. (rare earth BR synthesized using Nd-based catalyst, vinyl content: 0.7 mass%, cis content: 97 mass%, SP value: 8.2) <Carbon black>: Show Black N220 (N2SA: 114m) manufactured by CAPOTT Japan Co., Ltd. 2 / g) <Silica 1>: Ultrasil VN3 (N2SA: 175m) manufactured by Evonik Degussa 2 / g) <Silica 2>: Ultrasil U9000Gr (N2SA: 235m) manufactured by Evonik Degussa 2 / g) <Magnesium sulfate>: Prototype manufactured by Kyowa Chemical Industry Co., Ltd. (anhydrous magnesium sulfate, median particle size (median diameter): 7.3 μm, apparent specific gravity: 0.58 g / ml, solubility in water at room temperature (20°C): 255 g / 100 g water, moisture content: 0.1 mass%, N2SA: 9.0 m 2 / g, equivalent to a water-soluble filler with a median particle size of 100 μm or less and an apparent specific gravity of 0.70 g / ml or less) <Silane coupling agent>: Evonik Degussa Si75 (bis(3-triethoxysilylpropyl disulfide) <α-methylstyrene resin>: SYLVARESSA85 manufactured by Arizona Chemical (copolymer of α-methylstyrene and styrene, softening point: 85°C) <Terpene resin>: YS Resin TO125 (aromatic modified terpene resin, softening point: 125°C) manufactured by Yasuhara Chemical Co., Ltd. <Aroma oil>: AH-24 (aromatic process oil) manufactured by Idemitsu Kosan Co., Ltd. <wb16>: WB16 manufactured by Struktol (a mixture of fatty acid calcium, fatty acid amide and fatty acid amide ester, ash content 4.5%) <Stearic acid>: Beaded stearic acid "Tsubaki" manufactured by NOF Corporation <Anti-aging agent 1>: Antigen 6C (6PPD, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine) manufactured by Sumitomo Chemical Co., Ltd. <Anti-aging agent 2>: Nocrac 224 (TMQ, 2,2,4-trimethyl-1,2-dihydroquinoline polymer) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. <Paraffin wax>: Ozoace 0355 manufactured by Nippon Seiro Co., Ltd. <Zinc oxide>: Two types of zinc oxide manufactured by Hakusui Tech Co., Ltd. <Sulfur>: HK200-5 (powdered sulfur containing 5% oil) manufactured by Hosoi Chemical Industry Co., Ltd. <Vulcanization accelerator 1>: Noccela-NS (N-tert-butyl-2-benzothiazolyl sulfenamide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd. <Vulcanization accelerator 2>: Noccelaer D (diphenyl guanidine) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.

[0170] According to the compounding recipe shown in Table 1, chemicals other than sulfur and vulcanization accelerator were kneaded for 5 minutes at 150°C using a 1.7L Banbury mixer manufactured by Kobe Steel, Ltd. to obtain a kneaded product. Next, sulfur and vulcanization accelerator were added to the kneaded product obtained, and the mixture was kneaded for 5 minutes at 80°C using an open roll to obtain an unvulcanized rubber composition.

[0171] [Table 1]

[0172] The resulting unvulcanized rubber composition was molded into the shape of a cap tread, and laminated together with other tire components to prepare 16 green tires.

[0173] Half of the produced green tire was press-vulcanized as it was at 170° C. for 10 minutes to obtain a comparative tire (size: 225 / 50R17).

[0174] For the remaining raw tires, a 20% magnesium sulfate aqueous solution (same magnesium sulfate as above) was used, and the magnesium sulfate spray amount after drying was 0.01 g / cm 2 After drying, the mixture was press-vulcanized at 170° C. for 10 minutes in the same manner as in the comparative example to obtain a tire of the example (size: 225 / 50R17).

[0175] 2. Evaluation The obtained tires were evaluated for the following items. The evaluation was carried out twice: immediately after the tires were mounted and the vehicle started to travel, and after traveling 100 km.

[0176] (1) Grip performance on ice at low temperatures Using each tire, actual vehicle performance on ice was evaluated under the following conditions. The test was conducted at Sumitomo Rubber Industries, Ltd.'s Nayoro test course in Hokkaido, with temperatures ranging from -10 to -6°C. Each tire was fitted to a domestically produced 2000cc FR vehicle, and the stopping distance on ice required to apply the lock brakes and stop the vehicle at a speed of 30km / h was measured. The measured value after driving 100km for the comparative tire was used as a reference, and the results were expressed as an index using the following formula. The higher the index, the better the grip performance on low-temperature ice. (Grip performance on ice at low temperature) = (braking stopping distance of comparative tire after 100 km travel) / (stopping distance of each tire) x 100

[0177] (2) Grip performance on ice at high temperatures Using each tire, actual vehicle performance on ice was evaluated under the following conditions. The test was conducted at Sumitomo Rubber Industries, Ltd.'s Nayoro test course in Hokkaido, and the temperature was 0 to -5°C. The test tires were mounted on a domestically produced 2000cc FR vehicle, and the stopping distance on ice required to apply the lock brakes and stop the vehicle at a speed of 30km / h was measured. The measured value after driving 100km for the comparative tire was used as a reference, and the results were expressed as an index according to the following formula. The higher the index, the better the grip performance on high-temperature ice. (Grip performance on high-temperature ice) = (braking stopping distance of comparative tire after 100 km driving) / (stopping distance of each tire) × 100

[0178] The evaluation results are shown in Table 2. Also, an optical microscope photograph showing the results of observing the outermost surface of the tread immediately after running with a digital microscope (Keyence Corporation: VHX-6000) is shown in Figure 1 (observation conditions: ring illumination, magnification 500x).

[0179] [Table 2]

[0180] As shown in Table 2, it can be seen that the comparative tire does not exhibit sufficient performance immediately after mounting and running on ice at low temperatures and high temperatures.

[0181] The reason for this result is that immediately after mounting, a skin layer that contains almost no water-soluble filler is formed on the tread surface of the tire, which means that the tire does not exhibit sufficient grip performance on ice.

[0182] In contrast, it is clear that the tires of the examples exhibit sufficient grip performance on ice at low temperatures and on ice at high temperatures immediately after mounting.

[0183] The reason for this difference is that, as shown in Figure 1, in the tire of the comparative example immediately after mounting, a skin layer containing almost no water-soluble filler was formed on the tread surface, and there were almost no irregularities, so sufficient grip performance on ice was not exhibited, whereas in the tire of the example immediately after mounting, voids caused by the dissolved water-soluble filler formed irregularities on the tread surface, so sufficient grip performance on ice was exhibited.

[0184] Although the present invention has been described above based on the embodiment, the present invention is not limited to the above embodiment. Various modifications can be made to the above embodiment within the same and equivalent scope of the present invention.

Claims

1. The tread portion is formed by a tread main body portion made of a tread rubber composition and a surface layer portion made of a rubber composition having a higher polymer concentration than the tread rubber composition of the tread main body portion, The thickness of the surface layer is several tens to 100 μm, The pneumatic tire is characterized in that the surface layer portion contains 10 to 80 mass % of a water-soluble inorganic filler.

2. 2. The pneumatic tire according to claim 1, wherein the water-soluble inorganic filler in the surface layer portion of the tread portion is one or a mixture of two or more of a metal sulfate, a metal chloride, a metal hydroxide, a carbonate, and a phosphate.

3. 3. The pneumatic tire according to claim 2, wherein the water-soluble inorganic filler in the surface layer of the tread portion is a metal sulfate.

4. 4. The pneumatic tire according to claim 3, wherein the metal sulfate in the surface layer of the tread portion is magnesium sulfate.

5. 5. The pneumatic tire according to claim 4, wherein the magnesium sulfate is any one of anhydrous magnesium sulfate, magnesium sulfate dihydrate, and magnesium sulfate trihydrate, or a mixture of two or more of them.

6. 6. The pneumatic tire according to claim 1, wherein a water-insoluble inorganic filler is added to a surface layer portion of the tread portion in addition to the water-soluble inorganic filler.

7. The pneumatic tire according to claim 6, characterized in that a content ratio of the water-insoluble inorganic filler to the water-soluble inorganic filler is 3 to 30 mass %.

8. 8. The pneumatic tire according to claim 6, wherein the water-insoluble inorganic filler is one or a mixture of two or more of egg shells, zinc oxide needle crystals, rice husks, talc, magnesium oxide, and iron powder.

9. 9. The pneumatic tire according to claim 1, wherein the tread portion is a studless tire formed from a rubber composition containing a water-soluble inorganic filler.

10. 10. The pneumatic tire according to claim 9, wherein the studless tire is a studless tire for passenger cars.

11. A method for manufacturing a pneumatic tire, comprising, between a molding step of molding a raw tire and a vulcanization step of vulcanizing the molded raw tire, a step of spraying an inorganic filler on a surface of a tread portion of the molded raw tire.

12. 12. The method for manufacturing a pneumatic tire according to claim 11, wherein the inorganic filler spraying step is a step of spraying the water-soluble inorganic filler by applying an aqueous solution of the water-soluble inorganic filler onto a surface of the tread portion.

13. 12. The method for manufacturing a pneumatic tire according to claim 11, wherein the inorganic filler spraying step is a step of spraying the water-soluble inorganic filler by applying an organic solvent dispersion of the water-soluble inorganic filler onto a surface of the tread portion.

14. The method for producing a pneumatic tire according to claim 13, characterized in that the organic solvent in the organic solvent dispersion is selected from the group consisting of one or a mixture of two or more of a hydrocarbon organic solvent, anhydrous ethanol, and hexane.

15. The inorganic filler scattering step is carried out so that the amount of the water-soluble filler scattered on the surface of the tread portion after drying is 0.005 to 0.04 g / cm 2 and applying and spraying the aqueous solution of the water-soluble inorganic filler or the organic solvent dispersion of the water-soluble inorganic filler in an aqueous solution or an organic solvent dispersion of the water-soluble inorganic filler in an aqueous solution or an organic solvent dispersion of the water-soluble inorganic filler in an organic solvent.

16. 16. The method for producing a pneumatic tire according to claim 12, wherein a water-insoluble inorganic filler is added to the aqueous solution of the water-soluble inorganic filler or the organic solvent dispersion of the water-soluble inorganic filler.

Citation Information

Patent Citations

  • Production of semiconductor package

    JP1979056363A

  • Heat pipe type radiator

    JP1980092885A

  • Treatment of noxious metal-contg. waste water

    JP1983034086A

  • Tire

    JP2013147228A

  • Surface modification method and surface-modified elastic body

    JP2013159667A